Reporting of paediatric exercise-induced respiratory symptoms by physicians and parents: an observational prospective study - Eva S.L. Pedersen; Sarah Glick; Carmen C.M. de Jong; Cristina Ardura-Garcia; Anja Jochmann; Carmen Casaulta; Katharina Hartog; Diana Marangu-Boore; Dominik Mueller-Suter; Nicolas Regamey; Florian Singer; Alexander Moeller; et al. (Swiss Medical Weekly)
STUDY AIMS: Routinely collected health data are increasingly used for research; however important anamnestic details may be missing from medical records. We compared physician documentation of paediatric exercise-induced respiratory symptoms in clinical notes with parental questionnaire responses for the same children.